Simplification and Improvement of protein detection in two-dimensional electrophoresis gels with SERVA HPE™ Lightning Red. (July 2013) - Griebel, Anja; Obermaier, Christian; Westermeier, Reiner; Moche, Martin; Büttner, Knut
Abstract A new fluorescent amino-reactive dye has been tested for both labelling proteins prior to electrophoretic separations and between the two steps of two-dimensional electrophoresis. A series of experiments showed, that the labelling of lysines with this dye is compatible with all standard additives used for sample preparation, including reducing substances and carrier ampholytes. Using this dye for pre-labelling considerably simplifies the electrophoresis and detection workflow and provides highly sensitive and quantitative visualisation of proteins.